2004
DOI: 10.1097/01.qai.0000140604.57478.67
|View full text |Cite
|
Sign up to set email alerts
|

Prevention for Substance-Using HIV-Positive Young People

Abstract: HIV risky behaviors and health practices were examined among young people living with HIV (YPLH) in Los Angeles, San Francisco, and New York over 15 months in response to receiving a preventive intervention. YPLH aged 16 to 29 years (n = 175; 26% black and 42% Latino; 69% gay men) were randomly assigned to a 3-module intervention totaling 18 sessions delivered by telephone, in person, or a delayed-intervention condition. Intention-to-treat analyses found that the in-person intervention resulted in a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 26 publications
1
122
0
Order By: Relevance
“…Young women living with HIV would appear to benefit from targeted interventions that help them cope with their own feelings and fears about their HIV infection, which may be exacerbated by higher rates of emotional distress. The YPLH in this study have high levels of emotional distress (see Rotheram-Borus et al, 2004). Depressed persons make global, stable, and internal attributions about negative events.…”
Section: Discussionmentioning
confidence: 74%
“…Young women living with HIV would appear to benefit from targeted interventions that help them cope with their own feelings and fears about their HIV infection, which may be exacerbated by higher rates of emotional distress. The YPLH in this study have high levels of emotional distress (see Rotheram-Borus et al, 2004). Depressed persons make global, stable, and internal attributions about negative events.…”
Section: Discussionmentioning
confidence: 74%
“…At least one intervention has been shown to be effective in reducing HIV risk and drug use among younger persons. 24 The within-participant evidence for increases in high-risk sexual behavior during reporting periods characterized by increased use of methamphetamine, poppers, or sniffed cocaine suggests that, to reduce and prevent HIV, no level of use of these drugs should be considered "safe". There was no dose-response for drug use scores above 2, indicating that even intermittent, recreational use of these drugs is associated with high-risk sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…From 1999 to 2002, 175 YPLH aged 16 to 29 years (26% African American, 42% Latino; 69% gay young men; Table 1) were recruited with voluntary informed consent in Los Angeles, San Francisco, and New York City (Rotheram-Borus et al, 2004). Across cities, YPLH were recruited from medical providers, social service agencies, needle-exchange programs, a drugtreatment center, other research studies, outreach on the street or at special events, and through newspaper advertisements and word-of-mouth.…”
Section: Methodsmentioning
confidence: 99%
“…A full description of the study procedures are reported elsewhere (Rotheram-Borus et al, 2004). The intervention consisted of three modules of six sessions each and each session was approximately 2 h long.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation